EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN TEKNIK PSIKODRAMA UNTUK MENINGKATKAN EFIKASI DIRI SISWA KELAS VIII MTS - fitriani, fitriani; Samsudin, Asep; Sari, Resti Okta (IKIP Siliwangi, 2024)
This study aims to determine the effectiveness of group guidance using psychodrama techniques to increase the self-efficacy of class VIII MTS students. This study uses an experimental method with a quantitative approach. The total population in this study was 120 students of class VIII MTS Nurul Hidayah Miftahurroja with a sample of 12 students as the experimental group and 12 students as the control group. The research instrument used a questionnaire and observation sheet. Self-efficacy data were collected using a pretest-posttest questionnaire. The hypothesis test is seen from the results of the Independent sample t-test and to measure service effectiveness with the gain test. The results showed that there was effectiveness in group guidance using psychodrama techniques to increase students' self-efficacy from the results of the hypothesis test with a Sig (2-tailed) value found in Equal variance assumed worth 0.000 with a significance level of 0.05 (α=5%) . The results of the self-efficacy gain test obtained an n-gain score of 0.7750 in the high category and a percent n-gain of 77.5% in the effective category. Thus the gain results show that group counseling with the psychodrama technique is effectively used in increasing student self-efficacy.